Mental health in first- and second-division soccer players: A cross-sectional study - Bonet, L.; Benito, A.; Usó, H.; Peraire, M.; Haro, G.; Almodóvar-Fernández, I. (Sports, 2024)
Background: The benefits of sport in mental health have been broadly studied. However, few studies have examined these outcomes in high-performance athletes. We aimed to analyze the state of the mental health of the Villarreal Soccer Club`s first- (FD) and second-division (SD) players and the possible mediating effects of sex and professional category.